The Coexistence of Faith and Reason: Habermas’ Theoretical Framework of the Post-Secular Society - Tahrus, Zainun Nur Hisyam (Masyarakat: Jurnal Sosiologi, 2022)
The Post-Secular Society is a project put forward by Habermas as a critique of modern secularism. Habermas envisions this project as a via media—a mediating force between religious fundamentalism and excessive secularism. He argues that religious citizens can translate their religious discourses into a generally-accessible language that would enable them to discuss and communicate with their secular counterparts. This theory provides itself as an alternative to the Secularization Thesis, which had been the predominant framework for sociologists to study the relationship between the religious and the secular, or between faith and reason. This article attempts to outline sociological and philosophical foundations of Habermas’ Post-Secular Society by reviewing his essays and public speeches. As a counterbalance, the article will also present criticisms against Habermas’ notion of Discursive Translation and the limits of translation itself, which will function as a theoretical yardstick in gauging to what extent the Post-Secular Society is achievable. In conclusion, I argue that Habermas’ concept on the Post-Secular Society, whichhe argues to require religious communities to carry out Discursive Translation, can be realized within the moral-practice component of religion. However, this concept requires further conceptualization, especially when applied to non-European societies and religious life at the micro-level.